Implementasi Pelaksanaan Pengawasan Pembangunan oleh Dewan Perwakilan Rakyat Daerah (DPRD): Pembelajaran dari Kota Malang - Nurrizha Ayu; Asep Nurjaman (Nakhoda: Jurnal Ilmu Pemerintahan, 2022)
Good local governance can be realized by the implementation of the function of both the government and the Regional Representative Council (DPRD). To realize good national development results, it is necessary to supervise its implementation. The purpose of this study is to describe the supervision of DPRD in the implementation of development in Malang City. The research method used is the descriptive qualitative research method, where the research is carried out in the field in accordance with the existing facts. The research location is located in the office of Commission C of the Malang City DPRD and in the Malang Creative Center project. The results showed that the supervision carried out by the Malang City DPRD in the construction of the Malang Creative Center was carried out by going directly to the field. The implementation of the development goes according to the targets and requirements agreed upon in the contract agreement. Given the importance of supervision, the DPRD must always involve in the implementation of development in Malang City. Broadly speaking, Commission C of the Malang City DPRD did not get any problems from participants who participated in the construction of the Malang Creative Center.